Changes in cytomegalovirus load in the breast milk of very/extremely premature infants and the effect of pasteurization and freeze–thawing on reducing viral load - Huang, Tingting; Cai, Wenhong; Ni, Chen; Lai, Shuhua; Lin, Shuidi; Wang, Quangui (Frontiers in Pediatrics, 2022)
Objective:This study aimed to clarify the change in Cytomegalovirus(CMV) loads in breast milk(BM) of very/extremely premature infants(VPI/EPI) with birth weight <1500g after birth,and to compare the effectiveness of pasteurization and freeze–thawing methods in reducing the CMV load of BM.Methods:BM samples were collected and tested every 2 weeks by fluorescence quantitative polymerase chain reaction (FQ-PCR). We determined CMV load in BM before and after pasteurizing,and freeze-thawing.Results:CMV DNA can already be detected in colostrum.The viral load gradually increased in the first 4 weeks,peaked in the 4th to 6th weeks,and gradually decreased thereafter.The viral load gradually returned to the initial level approximately 10 to 12 weeks postpartum.During the peak period of the CMV load in BM,the viral load was higher in the EPI than the VPI (P<0.05).The average CMV load (logarithmic [LG]) in the pasteurization group was significantly lower than that in the raw BM group.The average CMV load in the freeze-thawed BM group was significantly lower than that in the raw BM group.The mean CMV load in the pasteurized BM group was lower than that in the freeze–thawed BM group,but the difference was not statistically significant.The CMV-DNA clearance rate in pasteurized was higher than in freeze–thawed (P<0.05).Conclusions:The CMV detoxification rate in BM is high and the peak load period is mainly between 4 and 6 weeks.The CMV load values detected are higher than the threshold values (7×10^3 copy number/mL) of CMV infection that are reported in the literature as a concern.Both the freeze-thaw and pasteurization techniques can effectively reduce the CMV load.